FOOD ALLERGY AND CROSS-ALLERGIC REACTIONS IN CHILDREN UNDER HOT CLIMATE - Abdullaev Asilbek Ongdalievich; Dauletbayev Asilbek Dauletbaevich; Abdullaeva Dilafruz Gayratovna (Scholar Express Journals, 2023)
To identify allergens that cause food allergies in children with allergic diseases using safe in vitro diagnostics.
Keywords: food allergy; children; food products